OECD Review of the Office for Budget Responsibility in the United Kingdom - von Trapp, Lisa (OECD Publishing, 2021)
This review examines the successes and challenges for the United Kingdom's Office for Budget Responsibility. It discusses its institutional context, its resources, its publications and underlying methodologies, and its impact on the public debate
Keywords: Economics; Finance and Investment; Governance; United Kingdom